Quality of Life and Psychiatric Comorbidities among Subjects Practicing Artificial Skin Depigmentation in 2020 in the City of Cotonou (Benin) - B. Degboe; M. M. D Baloubi; N. Ntouala Noukayaba; F. G. Akpadjan; H. Adegbidi; F. Atadokpede (Dermatology Research and Practice)
Introduction. The purpose of this study was to study the quality of life and psychiatric comorbidities of subjects practicing voluntary skin depigmentation in the city of Cotonou. Methods. A cross-sectional, prospective, and analytical study, based on a three-stage probabilistic sampling method, included from June to October 2020, consenting subjects over 15 years of age, practicing artificial skin depigmentation, and residing for at least one year in Cotonou. The Dermatology Life Quality Index, Rosenberg, and Hospital Anxiety and Depression scales allowed us to evaluate the quality of life and self-esteem, and identify anxiety and depression, respectively. A p value <0.05 indicated a significant result. Results. We included 330 subjects. The mean age was 33.6 ± 11.6 years and the sex ratio was 0.4. Impaired quality of life was observed in 93.7% of subjects. Anxiety was diagnosed in 11.2% and depression in 5.8% of them. Self-esteem was low or very low in 24.2%. The degree of quality of life and the alteration of self-esteem, and the frequency of anxiety and depression were proportional to the number of skin lesions, the lightening products used, and the monthly cost of the products. Conclusion. The use of several lightening products exposes patients to numerous skin lesions, which are a source of impaired quality of life and whose persistence leads to psychiatric comorbidities.